2024
DOI: 10.1093/jamia/ocae033
|View full text |Cite
|
Sign up to set email alerts
|

Genetically guided precision medicine clinical decision support tools: a systematic review

Darren Johnson,
Guilherme Del Fiol,
Kensaku Kawamoto
et al.

Abstract: Objectives Patient care using genetics presents complex challenges. Clinical decision support (CDS) tools are a potential solution because they provide patient-specific risk assessments and/or recommendations at the point of care. This systematic review evaluated the literature on CDS systems which have been implemented to support genetically guided precision medicine (GPM). Materials and Methods A comprehensive search was co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…While many research studies have examined integration of genetic testing into the management of cancer, 3 , 4 little has been done in other areas such as chronic kidney disease (CKD), which affects 1 in 7 US adults. 5 The diagnosis of CKD may benefit from improved integration of genetic testing as a monogenic cause may affect as many as 10% of patients with CKD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many research studies have examined integration of genetic testing into the management of cancer, 3 , 4 little has been done in other areas such as chronic kidney disease (CKD), which affects 1 in 7 US adults. 5 The diagnosis of CKD may benefit from improved integration of genetic testing as a monogenic cause may affect as many as 10% of patients with CKD.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Our systematic review highlighted the potential for clinical decision support (CDS) tools to improve the uptake of genetic services and the challenges in effectively implementing them, such as the reliance on alerts and reminders, lack of standards for genomic data integration, and underuse of implementation frameworks. 3 The review also demonstrated genetic CDS tools primarily focus on cancer and pharmacogenomics, indicating a knowledge gap in applying genotype and family history data for other specialties, such as nephrology. Scant attention has been paid to clinician needs and workflow, which has led to low adoption of genetic diagnosis.…”
Section: Introductionmentioning
confidence: 99%